A method for preparing nano-beryllium oxide

By using polymer compounds with different polymerization degrees and sonication treatment in the preparation of nanoberyllium oxide, a three-dimensional network structure polymer chain is formed, which solves the problems of uneven particle size and complex process of nanoberyllium oxide, and achieves the effect of uniform particle size distribution and simplified process.

CN116553583BActive Publication Date: 2025-03-25SHANGHAI TAIYANG TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310328585.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-03-25
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

In the prior art, the preparation process of nanoberyllium oxide is complex, the particle size is uneven, the baking temperature is high, the operation is not economical, and the environmental protection is difficult.

Method used

By using polymer compounds of different polymerization degrees to form a three-dimensional network structure polymer chain in the aqueous phase, and combining ultrasonic treatment and hydrothermal treatment, the particle size and distribution of beryllium oxide grains are regulated.

Benefits of technology

It achieves a more uniform particle size distribution of nanoberyllium oxide, a lower calcination temperature, simplified process, and improved environmental protection, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116553583B_ABST
    Figure CN116553583B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing nano beryllium oxide, comprising: S1. preparation of beryllium hydroxide suspension; S2. preparation of beryllium hydroxide gel; S3. hydrothermal pretreatment of beryllium hydroxide gel; S4. hydrothermal treatment; S5. formation of nano beryllium oxide. In the present invention, polymer compounds with different polymerization degrees are added in the step of S3 hydrothermal pretreatment, so that nano particles with different scale ranges can be synthesized; at the same time, polymer compounds with different polymerization degrees are used to optimize the interface and dissolution performance, which is further conducive to the particle size adjustment and uniformity regulation of nano beryllium oxide particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanometer beryllium oxide material preparation, in particular to a method for preparing nanometer beryllium oxide. Background Art

[0002] Beryllium oxide is a colorless hexagonal crystal of the hexagonal system, odorless and tasteless. It has good heat resistance, is stable at high temperatures, is difficult to be reduced, and has strong corrosion resistance. Compared with aluminum oxide, its thermal conductivity is about 7 times higher. Its dielectric constant is about half that of aluminum oxide. Its hardness is 9.0 (Mohs, diamond is 10). Beryllium oxide is mainly used in the fields of high heat generation and ultra-high frequency, especially in the lining materials of rocket combustion chambers; it is also used in the manufacture of neon lamps, fluorescent lamps, organic synthesis catalysts, beryllium alloys and refractory materials.

[0003] The preparation methods of micron-sized beryllium oxide include sulfuric acid method and fluorination method, both of which have the problems of long process, more equipment, difficult operation, low product quality and recovery rate, high requirements on raw material grade, large amount of waste residue and wastewater to be treated, and greater difficulty in environmental protection.

[0004] In recent years, with the development and use of nanomaterials, the demand for nano-beryllium oxide materials has increased. How to prepare nano-beryllium oxide with controllable and uniform particle size is a technical problem that needs to be solved urgently. Currently, the methods commonly used to prepare beryllium oxide nanomaterials include deposition method, microemulsion method and sol-gel method. However, there are technical problems such as high calcination temperature, uncontrollable particle size distribution, more organic solvents added, and uneconomical and environmentally friendly production process, which restrict the industrial scale-up production of beryllium oxide nanomaterials.

[0005] The applicant's previous patent CN114455615A discloses a method for preparing nano-beryllium oxide, but this method requires strict control of parameters such as the temperature and time of the programmed heating, the heating rate, etc., so as to avoid the aggregation of beryllium oxide nanoparticles, and the operation is complicated and the energy consumption is high. Therefore, we propose a method for preparing nano-beryllium oxide material. Summary of the invention

[0006] In order to solve the problems in the prior art that the preparation process of nano-beryllium oxide with uniform particle size is complicated or the obtained beryllium oxide particle size is not uniform, the present invention utilizes polymer compounds with different polymerization degrees, and uses the high-polymerization-degree polymer compounds to form stable three-dimensional network structure polymer chains, while the low-polymerization-degree polymer compounds are conducive to optimizing the dispersion performance, so that the molecular chains in the three-dimensional structure are easy to stretch, thereby making it difficult for the beryllium oxide grains to aggregate, and the final nano-beryllium oxide particle size distribution is more uniform.

[0007] The present invention provides a method for preparing nano-beryllium oxide, comprising the following steps:

[0008] S1. Preparation of beryllium hydroxide suspension: stirring and adding an organic amine to an aqueous beryllium sulfate solution, controlling the pH value of the suspension, continuing stirring, and allowing to stand for aging to obtain a suspension;

[0009] S2. Preparation of beryllium hydroxide gel: stirring the suspension, filtering and washing to obtain a gel;

[0010] S3. Hydrothermal pretreatment of beryllium hydroxide gel: The gel was dissolved in deionized water, and polymer compounds with different polymerization degrees and ammonium persulfate were added, stirred evenly, ultrasonically treated, and the mixture was transferred to a hydrothermal synthesis reactor;

[0011] S4. Hydrothermal treatment: controlling the hydrothermal synthesis temperature and reaction time;

[0012] S5. Formation of nano-beryllium oxide: After the hydrothermal treatment, the mixed solution is filtered and washed, and the obtained solid material is dried and calcined to obtain the nano-beryllium oxide material.

[0013] Preferably, in step S1, beryllium sulfate is used as the beryllium source and beryllium hydroxide is precipitated using an organic amine.

[0014] Weigh analytically pure BeSO4·4H2O powder and dissolve it in deionized water to obtain a beryllium sulfate aqueous solution with a concentration of 1.0-2.0 mol / L.

[0015] The organic amine used is selected from one of ethylenediamine, sec-butylamine, 1,2-propylenediamine, trioctylamine and tert-butylamine, and the dropping rate of the organic amine is controlled at 4-8 mL / min.

[0016] In step S1, the pH value of the suspension is 7.5-8.5, and stirring is continued for 30-60 minutes, after which the suspension is allowed to stand and age for 10-12 hours.

[0017] In step S3, the polymer compound is selected from polyvinyl pyrrolidone (PVP) or polyvinyl alcohol (PVA); and the different polymerization degrees are a compound of a low-polymerization-degree polymer compound and a high-polymerization-degree polymer compound.

[0018] The low-polymerization-degree polymer compound and the high-polymerization-degree polymer compound may be added simultaneously or in stages.

[0019] The types of polymer compounds with different degrees of polymerization may be the same or different.

[0020] That is, it can be low-polymerization PVP+high-polymerization PVP; low-polymerization PVA+high-polymerization PVA; low-polymerization PVP+high-polymerization PVA, or low-polymerization PVA+high-polymerization PVP. Preferably, it is low-polymerization PVA+high-polymerization PVP.

[0021] The amount of the low-polymerization-degree polymer compound added is 10-20 wt %, preferably 15-18 wt %, such as 16.7 wt %, of the total amount of the polymer compound.

[0022] Furthermore, the number average molecular weight of the low-polymerization degree polyvinyl pyrrolidone is 7000-10000 g / mol; the number average molecular weight of the high-polymerization degree polyvinyl alcohol pyrrolidone is 20000-50000 g / mol.

[0023] In one embodiment of the present invention, the number average molecular weight of the high polymerization degree polyvinyl pyrrolidone is 30000-58000; the number average molecular weight of the low polymerization degree polyvinyl pyrrolidone is 7000-10000.

[0024] The number average molecular weight of the low-polymerization degree polyvinyl alcohol is 10,000-35,000 g / mol; the number average molecular weight of the high-polymerization degree polyvinyl alcohol is 120,000-150,000 g / mol.

[0025] In one embodiment of the present invention, the molecular weight of the low-polymerization degree polyvinyl alcohol is 20,000 g / mol, and the molecular weight of the high-polymerization degree polyvinyl alcohol is 150,000 g / mol.

[0026] The invention forms a three-dimensional network structure polymer chain in the water phase by introducing a polymer and ammonium persulfate, and further refines the beryllium grains through ultrasonic treatment. The polymer can regulate the particle size and particle size dispersion of the beryllium oxide nanoparticles.

[0027] Preferably, the polymer compound with different polymerization degrees is a compound of low-polymerization degree polyvinyl alcohol and high-polymerization degree polyvinyl pyrrolidone. The inventors found that low-polymerization degree polyvinyl alcohol has a lower molecular weight and better solubility, and also has the effect of optimizing interfacial tension. High-polymerization degree polyvinyl pyrrolidone and ammonium persulfate form a stable three-dimensional network structure polymer chain in the aqueous phase, and at the same time, with the help of low-polymerization degree polyvinyl pyrrolidone, the dissolution and dispersion properties are optimized, so that the molecular chains in the three-dimensional structure are easy to stretch, and the molecular chain dispersion arrangement is optimized, so that the refined beryllium oxide grains are not easy to aggregate, and the particle size distribution of the nano beryllium oxide finally obtained is more uniform.

[0028] Therefore, the present invention optimizes the interface performance with the help of a small amount of low-polymerization-degree polymer compounds, and cooperates with the structural guidance effect of high-polymerization-degree polymer compounds to form a three-dimensional structure polymer chain with better stretch performance. Therefore, the method of the present invention not only regulates the particle size of beryllium oxide nanoparticles, but also makes the particle size distribution of nanoparticles more uniform, with good uniformity, which is more conducive to the preparation of nano beryllium oxide materials, thereby forming a beryllium oxide material with a more uniform particle size distribution. Furthermore, due to the use of polymer compounds with different polymerization degrees, the beryllium oxide nanoparticle size and distribution can be regulated during the nanoparticle formation process. Therefore, the present invention does not need to rely on a complex program temperature rise program, nor is it subject to excessive restrictions on the roasting temperature, which greatly simplifies the process and is conducive to industrial application and promotion.

[0029] Preferably, the mass ratio of beryllium hydroxide gel: polymer compound: ammonium persulfate: deionized water is 24-38: 2-3.5: 0.06-0.1: 100, the stirring temperature is 45-55° C., and the ultrasonic time is 20-40 min.

[0030] In step S4, the hydrothermal synthesis temperature is controlled at 150-180° C., and the reaction time is controlled at 24-48 h.

[0031] In step S5, the calcination temperature is 400-700° C., and the calcination time is 1-4 hours; the calcination is performed in a muffle furnace.

[0032] A stirring and dropping device for preparing nano-beryllium oxide materials of the present invention comprises a body, a stirring device, a dropping device, a driving device and a storage barrel, a control panel is provided on the body, a lifting block is slidably connected to the body, a support rod is fixedly connected to the lifting block, a stirring device is mounted on the support rod, and is used to stir the mixed solution in the storage barrel and detect the pH value of the suspension, a dropping device is mounted on the support rod, and is used to drop organic amines in the storage barrel, and a driving device is mounted on the lifting block, and is used to adjust the height position of the lifting block and can control the working state of the dropping device and the stirring device. The specific structure can refer to the content disclosed in the applicant's previous patent CN202210091798.X for raw material addition and parameter regulation.

[0033] Preferably, the stirring and dropping device for preparing nano-beryllium oxide material in the present invention comprises a body, a stirring device, a dropping device, a driving device and a storage barrel, wherein the body is provided with a control panel, the body is slidably connected with a lifting block, the lifting block is fixedly connected with a support rod, the stirring device is installed on the support rod, and is used to stir the mixed solution in the storage barrel and detect the pH value of the suspension, the dropping device is installed on the support rod, and is used to drop organic amine into the storage barrel, the driving device is installed on the lifting block, and is used to adjust the height position of the lifting block and can control the working state of the dropping device and the stirring device, and by arranging the stirring device, the dropping device and the driving device, it is convenient to strictly control the dropping and stirring rate of the organic amine, and at the same time, the function switching of dropping and stirring at the same time in the initial stage and continuing stirring for 30 to 60 minutes after the pH of the suspension is 7.5 to 8.5 can be realized, so that the preparation process is more accurate and convenient to use.

[0034] Beneficial effects achieved by the present invention:

[0035] (1) The present invention can synthesize nanoparticles of different size ranges by adjusting the type and addition ratio of the polymer compound; at the same time, the polymer compounds with different polymerization degrees are used to optimize the interface and solubility properties, which is further beneficial to the structure-directing effect of the polymer compound on the particle size adjustment and uniformity regulation of the nanoparticles.

[0036] (2) The present invention uses beryllium sulfate as a beryllium source, uses organic amines to precipitate beryllium hydroxide, and obtains beryllium hydroxide gel through aging and other steps; introduces polymer compounds with different polymerization degrees and ammonium persulfate to form a three-dimensional network structure polymer chain in the water phase, and further refines the beryllium grains under ultrasonic treatment conditions, making it difficult to agglomerate; hydrothermally treats the beryllium-containing mixed solution under certain conditions, and the insoluble matter is filtered, washed, dried and finally roasted to obtain a nano-beryllium oxide material. The roasting temperature of the nano-beryllium oxide material preparation process of the present invention is low, and there is no need to control the program temperature rise. The roasting process is simple to operate, and the average particle size of the nano-beryllium oxide finally obtained is within 10nm, and the particles are not aggregated.

[0037] (3) The hydrothermal method of the present invention is simple to operate, with less emissions of wastewater and waste gas, which meets the requirements of green environmental protection. The complicated programmed temperature increase steps can be avoided by simply adjusting the type of raw material added, effectively reducing particle size agglomeration, and can be suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a transmission electron microscope (TEM) image of nano-beryllium oxide prepared in Example 1;

[0039] Figure 2 This is a transmission electron microscope (TEM) image of nano-beryllium oxide prepared in Comparative Example 1. DETAILED DESCRIPTION

[0040] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0041] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0042] Example 1

[0043] A method for preparing nano-beryllium oxide specifically comprises the following steps:

[0044] (1) BeSO4·4H2O was weighed and dissolved in 350 mL of deionized water to prepare a 1.5 mol / L aqueous solution, 1,2-propylenediamine was added dropwise at a rate of 6.5 mL / min until the final pH was 8.0, and the mixture was stirred for 30 min and allowed to stand for aging;

[0045] (2) stirring the suspension evenly again after standing, filtering it with a vacuum filtration funnel and washing it with deionized water to obtain a milky white gel;

[0046] (3) Weigh 13.0 g of beryllium hydroxide gel, 0.2 g of low-polymerization degree polyvinyl pyrrolidone (K15, number average molecular weight 8000), 1.0 g of high-polymerization degree polyvinyl pyrrolidone (K25, number average molecular weight 24000), 0.04 g of ammonium persulfate and 43.3 g of deionized water in a beaker, stir evenly and ultrasonically treat at 50° C. for 30 min, and transfer the mixed solution to a hydrothermal synthesis reactor lined with polytetrafluoroethylene;

[0047] (4) Hydrothermal treatment conditions: 165 °C, 40 h;

[0048] (5) The mixed solution after the hydrothermal treatment is filtered, washed, and dried, and the obtained solid material is calcined at a high temperature, and the calcination temperature is maintained at 650° C. for 2.5 hours to finally obtain a nano-scale beryllium oxide material.

[0049] from Figure 1 It can be seen that the particle size distribution of the prepared beryllium oxide is very narrow, and the nanoparticles are mainly concentrated between 8nm and 9.5nm.

[0050] Example 2

[0051] A method for preparing nano-beryllium oxide specifically comprises the following steps:

[0052] (1) BeSO4·4H2O was weighed and dissolved in 400 mL of deionized water to prepare a 2 mol / L aqueous solution, and sec-butylamine was added dropwise at a rate of 8 mL / min until the final pH was 7.5. The mixture was stirred for 30 min and allowed to stand for aging;

[0053] (2) stirring the suspension evenly again after standing, filtering it with a vacuum filtration funnel and washing it with deionized water to obtain a milky white gel;

[0054] (3) Weigh 12.0 g of beryllium hydroxide gel, 0.1 g of low-polymerization degree polyvinyl pyrrolidone (K15, number average molecular weight 8000), 0.9 g of high-polymerization degree polyvinyl pyrrolidone (K30, molecular weight 38000), 0.03 g of ammonium persulfate and 31.8 g of deionized water in a beaker, stir evenly and ultrasonically treat at 55°C for 30 min, and transfer the mixed solution to a hydrothermal synthesis reactor lined with polytetrafluoroethylene;

[0055] (4) Hydrothermal treatment conditions: 180 °C, 48 h;

[0056] (5) The mixed solution after the hydrothermal treatment is filtered, washed, and dried, and the obtained solid material is calcined at a high temperature of 700° C. for 1.5 h to finally obtain a nano-scale beryllium oxide material.

[0057] Example 3

[0058] A method for preparing nano beryllium oxide material comprises the following steps:

[0059] (1) BeSO4·4H2O was weighed and dissolved in 300 mL of deionized water to prepare a 1 mol / L aqueous solution, and ethylenediamine was added dropwise at a rate of 4 mL / min until the final pH was 8.5. The mixture was stirred for 60 min and allowed to stand for aging;

[0060] (2) stirring the suspension evenly again after standing, filtering it with a vacuum filtration funnel and washing it with deionized water to obtain a milky white gel;

[0061] (3) Weigh 10.0 g of beryllium hydroxide gel, 0.1 g of low-polymerization degree polyvinyl pyrrolidone (K15, number average molecular weight 8000), 0.85 g of high-polymerization degree polyvinyl pyrrolidone (K25, number average molecular weight 24000), 0.04 g of ammonium persulfate and 41.2 g of deionized water in a beaker, stir evenly and ultrasonically treat for 30 min at 45°C, and transfer the mixed solution to a hydrothermal synthesis reactor lined with polytetrafluoroethylene;

[0062] (4) Hydrothermal treatment conditions: 150 °C, 36 h;

[0063] (5) The mixed solution after the hydrothermal treatment is filtered, washed, and dried, and the obtained solid material is calcined at a high temperature of 600° C. for 2 h to finally obtain a nano-scale beryllium oxide material.

[0064] Example 4

[0065] A method for preparing nano-beryllium oxide specifically comprises the following steps:

[0066] (1) BeSO4·4H2O was weighed and dissolved in 350 mL of deionized water to prepare a 1.5 mol / L aqueous solution, and ethylenediamine was added dropwise at a rate of 6.0 mL / min until the final pH was 7.5. The mixture was stirred for 40 min and allowed to stand for aging;

[0067] (2) stirring the suspension evenly again after standing, filtering it with a vacuum filtration funnel and washing it with deionized water to obtain a milky white gel;

[0068] (3) Weigh 26.2 g of beryllium hydroxide gel, 0.4 g of low-polymerization degree polyvinyl pyrrolidone (K15, number average molecular weight 8000), 2.0 g of high-polymerization degree polyvinyl pyrrolidone (K25, number average molecular weight 24000), 0.09 g of ammonium persulfate and 92 g of deionized water in a beaker, stir evenly and ultrasonically treat at 50° C. for 20 min, and transfer the mixed solution to a hydrothermal synthesis reactor lined with polytetrafluoroethylene;

[0069] (4) Hydrothermal treatment conditions: 170 °C, 25 h;

[0070] (5) The mixed solution after the hydrothermal treatment is filtered, washed, and dried, and the obtained solid material is calcined at a high temperature. The calcination temperature is maintained at 680° C. for 2 hours to finally obtain a nano-scale beryllium oxide material.

[0071] Example 5

[0072] The preparation method is the same as that of Example 1, except that: in step (3), 13.0 g of beryllium hydroxide gel, 0.2 g of low-polymerization degree polyvinyl alcohol (number average molecular weight 20,000), 1.0 g of high-polymerization degree polyvinyl alcohol (number average molecular weight 120,000), 0.04 g of ammonium persulfate and 43.3 g of deionized water are weighed in a beaker, stirred evenly at 50° C. and ultrasonically treated for 30 min, and the mixed solution is transferred to a polytetrafluoroethylene-lined hydrothermal synthesis reactor.

[0073] Finally, nano-scale beryllium oxide material is obtained.

[0074] Example 6

[0075] A method for preparing nano-beryllium oxide specifically comprises the following steps:

[0076] The preparation method is the same as that of Example 1, except that: in step (3), 13.0 g of beryllium hydroxide gel, 0.2 g of low-polymerization degree polyvinyl pyrrolidone (number average molecular weight 20,000), 1.0 g of high-polymerization degree polyvinyl alcohol (number average molecular weight 120,000), 0.04 g of ammonium persulfate and 43.3 g of deionized water are weighed in a beaker, stirred evenly at 50° C. and ultrasonically treated for 30 min, and the mixed solution is transferred to a hydrothermal synthesis reactor lined with polytetrafluoroethylene.

[0077] Finally, nano-scale beryllium oxide material is obtained.

[0078] Example 7

[0079] A method for preparing nano-beryllium oxide specifically comprises the following steps:

[0080] (1) BeSO4·4H2O was weighed and dissolved in 350 mL of deionized water to prepare a 1.5 mol / L aqueous solution, 1,2-propylenediamine was added dropwise at a rate of 7 mL / min until the final pH was 8.0, and the mixture was stirred for 40 min and allowed to stand for aging;

[0081] (2) stirring the suspension evenly again after standing, filtering it with a vacuum filtration funnel and washing it with deionized water to obtain a milky white gel;

[0082] (3) 13.0 g of beryllium hydroxide gel, 0.2 g of low-polymerization degree polyvinyl alcohol (number average molecular weight 20,000), 1.0 g of high-polymerization degree polyvinyl pyrrolidone (number average molecular weight 50,000), 0.04 g of ammonium persulfate and 43.3 g of deionized water were weighed into a beaker, stirred evenly and ultrasonically treated at 50° C. for 30 min, and the mixed solution was transferred to a hydrothermal synthesis reactor lined with polytetrafluoroethylene;

[0083] (4) Hydrothermal treatment conditions: 165 °C, 40 h;

[0084] (5) The mixed solution after the hydrothermal treatment is filtered, washed, and dried, and the obtained solid material is calcined at a high temperature, and the calcination temperature is maintained at 650° C. for 2.5 hours to finally obtain a nano-scale beryllium oxide material.

[0085] Comparative Example 1

[0086] The other steps are the same as those in Example 1, except that only a single polyvinyl pyrrolidone is used in step (3): 13.0 g of beryllium hydroxide gel, 1.2 g of polyvinyl pyrrolidone (K15, number average molecular weight 8000), 0.04 g of ammonium persulfate and 43.3 g of deionized water are weighed in a beaker, stirred evenly at 50° C. and ultrasonically treated for 30 min, and the mixed solution is transferred to a hydrothermal synthesis reactor lined with polytetrafluoroethylene.

[0087] from Figure 2 It can be seen that the particle size of the prepared nano-beryllium oxide particles is concentrated between 7-12 nm, but the particle size distribution is not uniform, and there is a tendency for particle size aggregation, and the uniformity of the nano-beryllium oxide particles cannot be effectively controlled.

[0088] Comparative Example 2

[0089] The other steps are the same as those in Example 1, except that only single polyvinyl pyrrolidone is used in step (3): 13.0 g of beryllium hydroxide gel, 1.2 g of polyvinyl pyrrolidone (K25, number average molecular weight 24000), 0.04 g of ammonium persulfate and 43.3 g of deionized water are weighed in a beaker, stirred evenly at 50° C. and ultrasonically treated for 30 min, and the mixed solution is transferred to a hydrothermal synthesis reactor lined with polytetrafluoroethylene.

[0090] Finally, nano-scale beryllium oxide material is obtained.

[0091] Comparative Example 3

[0092] The preparation method is the same as that of Example 1, except that: in step (3), 13.0 g of beryllium hydroxide gel, 1.2 g of low-polymerization degree polyvinyl alcohol (number average molecular weight 20,000), 0.04 g of ammonium persulfate and 43.3 g of deionized water are weighed in a beaker, stirred evenly at 50° C. and ultrasonically treated for 30 min, and the mixed solution is transferred to a hydrothermal synthesis reactor lined with polytetrafluoroethylene.

[0093] Finally, nano-scale beryllium oxide material is obtained.

[0094] Comparative Example 4

[0095] The preparation method is the same as that of Example 1, except that: in step (3), 13.0 g of beryllium hydroxide gel, 1.2 g of high-polymerization degree polyvinyl alcohol (number average molecular weight 120,000), 0.04 g of ammonium persulfate and 43.3 g of deionized water are weighed in a beaker, stirred evenly at 50° C. and ultrasonically treated for 30 min, and the mixed solution is transferred to a polytetrafluoroethylene-lined hydrothermal synthesis reactor.

[0096] Finally, nano-scale beryllium oxide material is obtained.

[0097] Nano Beryllium Oxide Performance Test

[0098] The beryllium oxide prepared in the examples and comparative examples was tested as follows:

[0099] (1) Structural morphology: The structural morphology of nanoparticles was observed using a transmission electron microscope;

[0100] (2) Average particle size and particle size distribution: The average particle size D50 and particle size distribution (D90-D10) / D50 of beryllium oxide measured by Nano Measure software are shown in Table 1.

[0101] Table 1

[0102] Average particle size D50 Particle size distribution (D90-D10) / D50 Example 1 8.8nm 1.23 Example 2 9.0nm 1.22 Example 3 9.2nm 1.36 Example 4 8.9nm 1.41 Example 5 8.7nm 1.39 Example 6 8.0nm 1.20 Example 7 8.2nm 1.12 Comparative Example 1 9.4nm 2.26 Comparative Example 2 10.0nm 1.78 Comparative Example 3 9.8nm 2.42 Comparative Example 4 9.0nm 1.85

[0103] Analysis of the data in Table 1 shows that the average particle size D50 of beryllium oxide prepared in Examples 1-7 of the present invention is within 10 nm, and the particle size distribution (D90-D10) / D50 is relatively narrow.

[0104] In Examples 1-4 of the present invention, nanoparticles of different size ranges can be synthesized by adjusting the type and addition ratio of polyvinyl pyrrolidone; at the same time, polyvinyl pyrrolidone with a low degree of polymerization is used to optimize the interface and solubility performance, which is further beneficial to the particle size adjustment and uniformity regulation of the nanoparticles by polyvinyl pyrrolidone, so that the refined beryllium oxide grains are not easy to aggregate, and the particle size distribution of the nano beryllium oxide finally obtained is more uniform, is not subject to the temperature control limit of high-temperature calcination, and can effectively control the particle size aggregation. The method is simple to operate and easy to control, which is conducive to industrial application.

[0105] Similarly, Example 5 uses polyvinyl alcohol with different polymerization degrees to synthesize nanoparticles with different size ranges, and finally obtains nanoberyllium oxide with uniform particle size distribution.

[0106] The particle size distribution (D90-D10) / D50 of beryllium oxide prepared in Examples 6-7 is narrower, presumably because there is an interaction force (such as hydrogen bonding) between different types of polymer compounds, which makes it easier to form a tight and stable three-dimensional network structure with ammonium persulfate in the aqueous phase, making the size of the beryllium oxide precursor smaller, so the final nano beryllium oxide particle size is smaller and the particle size distribution is narrower. In particular, Example 7 uses polyvinyl alcohol with a low degree of polymerization and polyvinyl pyrrolidone with a high degree of polymerization, and with the help of the network interaction force between different polymer compounds, the nano beryllium oxide particle size is smaller and the particle size distribution is narrower.

[0107] Comparative Examples 1-4 use polymer compounds with a single degree of polymerization. Although the particle size of nano-beryllium oxide can be controlled within 12 nm, the particle size distribution (D90-D10) / D50 is wide, the distribution is uneven, and the particles are obviously aggregated. Therefore, the calcination temperature and program heating parameters must be strictly controlled to solve this problem, which is not conducive to industrial production and application.

[0108] Those skilled in the art should understand that the above embodiments are only for the purpose of clearly illustrating the present disclosure, and are not intended to limit the scope of the present disclosure. For those skilled in the art, other changes or modifications may be made based on the above disclosure, and these changes or modifications are still within the scope of the present disclosure.

Claims

1. A method for preparing nano-beryllium oxide, characterized in that: The following steps are involved: S1. Preparation of beryllium hydroxide suspension: stirring and adding an organic amine to an aqueous beryllium sulfate solution, controlling the pH value of the suspension, continuing stirring, and allowing to stand for aging to obtain a suspension; S2. Preparation of beryllium hydroxide gel: stirring the suspension, filtering and washing to obtain a gel; S3. Hydrothermal pretreatment of beryllium hydroxide gel: dissolving the gel in deionized water, adding polymer compounds with different degrees of polymerization and ammonium persulfate, stirring evenly, ultrasonically treating, and transferring the mixture to a hydrothermal synthesis reactor; S4. Hydrothermal treatment: controlling the hydrothermal synthesis temperature and reaction time; S5. Formation of nano-beryllium oxide: After the hydrothermal treatment, the mixed solution is filtered and washed, and the obtained solid material is dried and calcined to obtain a nano-beryllium oxide material; The polymer compounds with different polymerization degrees are a compound of low-polymerization degree polyvinyl pyrrolidone and high-polymerization degree polyvinyl pyrrolidone; or a compound of low-polymerization degree polyvinyl alcohol and high-polymerization degree polyvinyl pyrrolidone; or a compound of low-polymerization degree polyvinyl pyrrolidone and high-polymerization degree polyvinyl alcohol; The amount of low-polymerization-degree polymer compound added accounts for 10-20wt% of the total amount of polymer compound; The number average molecular weight of the low-polymerization degree polyvinyl alcohol is 10000-35000 g / mol, and the number average molecular weight of the high-polymerization degree polyvinyl alcohol is 120000-150000 g / mol; The number average molecular weight of the low-polymerization degree polyvinyl pyrrolidone is 7000-10000 g / mol; the number average molecular weight of the high-polymerization degree polyvinyl alcohol pyrrolidone is 20000-50000 g / mol.

2. The method for preparing nano-beryllium oxide according to claim 1, wherein In step S1, BeSO4·4H2O powder is weighed and dissolved in deionized water to obtain a beryllium sulfate aqueous solution, wherein the concentration of the beryllium sulfate aqueous solution is 1.0 to 2.0 mol / L; The organic amine used is selected from one of ethylenediamine, sec-butylamine, 1,2-propylenediamine, trioctylamine and tert-butylamine, and the dropping rate of the organic amine is controlled at 4-8 mL / min.

3. The method for preparing nano-beryllium oxide according to claim 1, wherein In step S1, the pH value of the suspension is 7.5-8.5, and stirring is continued for 30-60 minutes, after which the suspension is allowed to stand and age for 10-12 hours.

4. The method for preparing nano-beryllium oxide according to claim 1, wherein In step S3, the mass ratio of beryllium hydroxide gel: polymer compound: ammonium persulfate: deionized water is 24-38: 2-3.5: 0.06-0.1:

100.

5. The method for preparing nano-beryllium oxide according to claim 1, characterized in that: In step S4, the hydrothermal synthesis temperature is controlled at 150-180° C., and the reaction time is controlled at 24-48 h.

6. The method for preparing nano-beryllium oxide according to claim 1, characterized in that: In step S5, the calcination temperature is 400-700° C., and the calcination time is 1-4 hours; the calcination is performed in a muffle furnace.

7. The nano-beryllium oxide material obtained according to the method for preparing nano-beryllium oxide according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Preparation method of nanometer beryllium oxide material

    CN114455615A